Interaction between the model of the social worker professional activity in the territorial community and the model of his professional training in the HEIs - Слозанська, Г. І. (Scientific notes of the pedagogical department, 2018)
The article is dedicated to the analysis of the interaction between the model of the social worker professional activity in the territorial community and the model of his professional training in the higher educational establishments. Ukraine is on the stage of territorial reforms which leads to the changes in social work and social workers activity. Due to the reforms that are taking place social workers have to work at the level of local communities providing services for people in need. As this process have just started to be there are no social workers completely ready to serve at the local community levels. There is no strict idea what these specialists have to do.So, Ukrainian scientists search foreign and home experience concerning the problem of providing services at the level of local community, point out main and important ideas for implementing in Ukraine. The content, functions, duties, roles of social workers at the level of local communities are also important as they serve like the base for developing social work programs in higher educational establishments, oriented on professional training of specialists ready to provide services at the level of local community.Having an idea of what social workers have to do at the level of local community the developers of social work programs how to build it, what subjects to plan, what practice should be. To be in time and train specialists according to the needs of labor market higher educational establishments have to base on the model of social worker professional activity when plan social work program.The main approaches to understanding model, model of professional activity and model of specialist are described in the article. It has been shown the connection of then with the process of making the model of future social workers training if Ukrainian higher educational establishments ready to provide services at the level of local community.